Is community-based management of small-scale fisheries in Sierra Leone the answer to their problems?. (March 2021) - Okeke-Ogbuafor, Nwamaka; Gray, Tim
Highlights: With the increasing decline in global fish stocks community-based approach to the governance of small-scale fisheries (SSFs) is becoming very popular. This study investigates the viability of this approach. It concludes that both government and community-based approaches to SSF have flaws yet, both need to work together. Community-based approach to coastal fisheries management is no guarantee of successful governance of this sector, instead, only the central government has the authority to impose a regime of equitable regulation on the country's inshore fisheries. Abstract: With increasing decline in global fish stocks and the possibility of extinction of many small-scale fisheries (SSF) partly because of over-fishing by large-scale industrial fishers (both licensed and unlicensed) and partly because of harmful fishing gear used by small-scale fishers themselves, researchers are focusing on alternatives to the prevailing top-down systems of fisheries management. One such alternative that is receiving attention is the community-based approach to the governance of SSF, which maintains that small-scale or artisanal fishers have a special attachment to their geographical area which makes them better managers of their fish resources. This study investigates the viability of this approach in Sierra Leone's Tombo and Goderich fishing communities. Fieldwork was carried out during 2017 and 2019 when a total of 51 key informant (KI) and 14 telephone interviews (TI) were conducted, and 200 survey questionnaires (SQ) were distributed in the two communities. The main finding is that although several community fisheries organisations (CFO) try to manage coastal stocks, they have no power to curb industrial over-fishing, and their power to stop artisanal fishers using harmful gear is compromised by government interference and by conflicts between CFOs. The study concludes that both top-down (governmental) and bottom-up (communitarian) approaches to SSF management have flaws, and each side needs to acknowledge its flaws, and work together with the other side to eliminate them.